Strengthening Scouting Character Values through a Moral Integrated Approach for Elementary School Students - Hasriani, Hasriani; Hamim, Udin; Mahmud, Ramli (Indonesian Journal of Innovation Studies, 2025)
General Background: Character education remains a foundational pillar in Indonesia's basic education system, emphasizing the holistic development of students beyond cognitive achievement. Specific Background: Scouting activities have long been viewed as a vehicle for instilling core values in students, yet their implementation often lacks an integrative moral framework. Knowledge Gap: Despite recognition of its potential, limited empirical studies have examined how scouting extracurriculars can systematically integrate moral knowing, moral feeling, and moral action. Aim: This study analyzes the implementation of scouting-based character education at SD Negeri 9 East Sumalata, North Gorontalo Regency, using a qualitative approach. Results: The findings indicate that effective character development requires the alignment of moral cognition, emotional engagement, and actionable behavior, supported by two main factors: parental involvement and a conducive school environment. Novelty: The study identifies a four-pillar collaboration model involving students (via participatory PRODIK programs), Scout coaches (as facilitators of nature-based learning and core principles), teachers (as curriculum integrators), and parents (as value reinforcers). Implications: These findings underscore the need for systemic and sustainable strategies, including structured training and evaluative mechanisms based on measurable character indicators, to foster cohesive character education in primary schools. Highlights: Highlights the synergy of school, family, and extracurriculars in shaping student character. Emphasizes integration of moral knowing, feeling, and action for effective character building. Proposes a four-pillar collaboration model for sustainable character education implementation Keywords: Character Education, Scout Extracurriculars, Moral Integration, Elementary School, Educational Collaboration